Addition to the Distributional Record of Ageniella (Neotumagenia) amazonica Fernández, 1998 (Hymenoptera: Pompilidae) and Establishment of a Neotype. (17th May 2012) - Waichert, Cecilia; Pitts, James P.
Abstract : Ageniella is a diverse and poorly studied genus in Ageniellini (Pompilidae: Pepsinae). It is composed of nine subgenera with four being endemic to the Neotropical region. Herein, the second record in the literature for the subgenus Neotumagenia is documented, the distribution range is extended, and a neotype is established. This is the first record of this subgenus in Brazil.